Multimodality Treatment of Early-Stage Tonsil Cancer. (July 2017) - Roden, Dylan F.; Schreiber, David; Givi, Babak
Objective: Compare survival outcomes between unimodality and multimodality treatments for early-stage tonsil squamous cell carcinoma (SCC). Study Design and Setting: Review of the National Cancer Database. Subjects and Methods: Patients were selected if they were <70 years old with clinical stage I-II SCC of the tonsil, as documented in the National Cancer Database from 1998 to 2011. Palliative and nonstandard treatments were excluded. Propensity score matching was performed, controlling for tumor stage, age, race, comorbidity, insurance status, and year of diagnosis. Overall survival (OS) was compared with the Kaplan-Meier method and log-rank test. Results: We identified 3247 patients. Radiotherapy (RT) was delivered in 1295 patients (39.9%), surgery in 824 (25.4%), and surgery + RT in 1128 (34.7%). Patients treated with surgery + RT had the highest 5-year OS (81.1%), followed by surgery (67.4%) and RT (63.4%; P < .001). In a propensity score–matched subpopulation of 2378 patients, the 5-year OS was 78.8% for surgery + RT, 66.7% for surgery, and 64.5% for RT ( P < .001). Among patients who underwent surgical tonsillectomy plus elective neck dissection and/or adjuvant RT, the 5-year OS was equal ( P = .29), and all were superior to RT alone ( P < .001). Conclusion: Multimodality treatment is associated with the greatest survival in early-stage tonsil cancer. The addition of tonsillectomy to RT confers a 20% increase in survival. The current guidelines might not offer the most effective treatment. An up-front surgical approach, followed by appropriately selected adjuvant therapy, may result in improved survival for early-stage tonsil SCC. These findings merit investigation in a prospective clinical trial.